The healthy eating and active time club curriculum teaching children to live well - Economos, Christina 1965-; Collins, Jessica; Hauser, Sonya Irish; Hennessy, Erin; Hudson, David; Kappelhof, Erin Boyd; Klemmer, Sandra; Kozower, Claire; Marcotte, Lori (Human Kinetics, 2014)
Helps children understand what a healthy diet is and how to stay physically active every day. This book teaches them how to make healthier nutrition and activity choices and discover how healthy eating and regular physical activity keep them feeling their best